Peningkatan Kemampuan Motorik Halus Anak Tunagrahita Melalui Penerapan Finger Painting Di SLB Laniang Makassar - Dini Meilani Pramesti; Syamsuddin, Syamsuddin; Hadis, Abdul (Primera Educatia Mandalika: Elementary Education Journal, 2024)
This research examines fine motor skills in mentally retarded children in class III of elementary school at SLB Laniang Makassar. The aims of this research are (1) Fine motor skills of mentally retarded children before being given intervention (baseline 1/A1), (2) Fine motor skills of mentally retarded children when given intervention (B), (3) Fine motor skills of mentally retarded children after being given intervention (baseline 2 (A2) baseline 2/A2). The data collection technique used was an action test. The subject in this study was a mentally retarded child in class III of elementary school at SLB Laniang Makassar CJ. This research used an experimental method using Single Subject Research (SSR) with an A-B-A design. The conclusions of this study: (1) before being given treatment it was very low based on baseline condition 1 (A1), (2) during the intervention it increased to the very high category seen from the analysis in intervention condition (B), (3) after being given the intervention to high category seen from baseline condition 2 (A2), (4) Fine motor skills in children based on analysis between conditions, namely: from very low category increased to very high category during intervention and from very high category decreased to high category. Thus, the child's fine motor skills after being given the intervention decreased, but the scores obtained were higher than before the intervention was given.